Modern rain-isotope data from Indian island and the mainland on the daily scale for the summer monsoon season - Nitesh Sinha; S. Chakraborty; P.M. Mohan (Data in Brief, 2019)
The atmospheric stable isotopes in rainwater are measured as the ratio of heavy to the lighter (e.g., 18O/16O). This data article describes two datasets of daily rain isotopic variations during the Indian Summer Monsoon (ISM) season. Firstly, an island site (namely Port Blair) dataset for four years (2012–2015) and another dataset of Indian mainland sites (namely Nagpur, Tezpur, and Kolkata) for the year 2015. Port Blair is strategically situated in the Bay of Bengal (BoB), which is known to be a significant moisture source to ISM rainfall over the Indian landmass. On the other hand, sites in the mainland are receivers of the BoB moisture. This dataset includes 1030 isotopic analyses made on daily water samples as well as rainfall amount (24 hours) during ISM.The data is related to “Isotopic investigation of the moisture transport processes over the Bay of Bengal” [1]. Keywords: Stable rain isotopes, Indian summer monsoon, Bay of Bengal